Teens and Dating: Tips for Parents - Kate Fogarty; Donna Davis (EDIS, 2012)
“I’ll never forget the initial shock I felt when my second grader came home from school one day to tell me that one of her friends was “going out” with one of the little boys in her class. “Going out?!” I asked. “What does that mean?” She couldn’t really answer, much to my relief. Many parents might likewise find themselves unprepared when they first learn their elementary and middle schoolers have developed perfectly normal crushes on their classmates.” This 2-page Family Album Radio transcript was written by Kate Fogarty and Donna Davis, and published by the UF Department of Family, Youth and Community Sciences, March 2012.